(untitled) (Annals of Medical Research, 2023)
Aim: Non-alcoholic fatty liver disease (NAFLD) has recently become a significant public health problem around the world, with a reported prevalence of 25%. In this study, we aimed to investigate the utility of biochemical and hematological markers in the progression from hepatosteatosis to fibrosis and to examine their superiority to each other by comparing them with pathological scoring parameters. Materials and Methods: Pathological results of patients who underwent liver biopsy for different indications were reviewed retrospectively.Of these, 120 patients with fatty liver were selected and their biopsy specimens were re-evaluated according to the NAFLD Activity Score (NAS). The relationship between pathological scores and serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST to platelet ratio index (APRI), red blood cell distribution width (RDW), neutrophil-to-lymphocyte ratio (NLR), RDW to platelet ratio (RPR), and gamma-glutamyl transpeptidase (GGT), RDW to platelet ratio (RPR), and gamma-glutamyl transpeptidase (GGT) was analyzed. Results: The results indicated that ALT, APRI, and GGT were significant predictors of nonalcoholic steatohepatitis (NASH), while GGT, APRI, and RPR were significant predictors of fibrosis. Additionally, ROC analysis confirmed the significant predictive value of APRI, RPR, and GGT in the diagnosis of fibrosis. Conclusion: Based on these results, we consider that GGT and APRI are better predictors than other biomarkers.